Ugo Cerletti (1877–1963): An Early Italian Father of Electroshock and a Pioneer in Many Other Ways. (October 2021) - Kotsaki, Konstantina; Diamantis, Aristidis; Magiorkinis, Emmanouil
This article provides a biographical review of the life and the professional achievements of the Italian doctor Ugo Cerletti and an introduction on electroshock. Throughout his medical career, he travelled and studied in many countries all over the world. Building upon his systematic and comprehensive analysis of mental diseases, Cerletti introduced electroshock, which, at his time, was a novel therapeutic method. The main beneficial feature of electroshock was that it ameliorated refractory mental illnesses such as depression, mania, and schizophrenia. Additionally, Cerletti filmed the first scientific movie on electroshock. Furthermore, Cerletti left great lessons in the area of dementia, by proving the interaction between spirochaetes and progressive paralysis and exploring the causes of inflammation in the syphilitic brain. Cerletti was the first to announce the theory of acroagonines. Cerletti also made early discoveries on perivascular corpuscles, a discovery of such importance that the perivascular corpuscles are named corpuscles of Cerletti. Outside of the medical realm, Cerletti invented a new type of gun, and produced an early medical documentary. Cerletti received many national and international distinctions and awards. He died in 1963 at the age of 86.